The Effect of Earning Per Share, Price to Book Value, Dividend Payout Ratio, and Net Profit Margin on the Stock Price in Indonesia Stock Exchange - Bustani Bustani; Kurniaty Kurniaty; Rahmi Widyanti (Universitas Proklamasi 45, 2021)
Fundamental analysis of companies with financial ratios is essential in making investment decisions for any company. Therefore, to obtain maximum profit, investors need to perform a study before making investment decisions. This research aims to examine the effect of Earning Per Share (EPS), Price to Book Value (PBV), Dividend Payout Ratio (DPR), and Net Profit Margin (NPM) on the stock price. The research at the Indonesia Stock Exchange, a sub-sector of food and beverage companies, period five years (2014-2018). The sample of this study amounted to 12 companies from 26 companies in the population of food and beverage companies that have met the researchers' criteria. Data analysis with bootstrapping used SEM (statistical equation modeling) in hypothesis testing. The research findings confirmed the significant effect of Earning per Share, Price to Book Value, and Dividend Payout Ratio on stock prices. Meanwhile, the Net Profit Margin does not significantly affect stock prices in the study period, with an alpha significance of five percent. These findings imply practical implications that EPS, PBV, DPR, and NPM ratio information can be considered in investment decisions for anyone.